Reflections on the US College Loans System: Lessons from Australia and England - Nicholas Barr; Bruce Chapman; Lorraine Dearden; Susan Dynarski (Institute of Labor Economics (IZA), 2018)
There is wide agreement the US student loan system faces significant problems. Seven million borrowers are in default and many more experience non-repayment. The stress of repayments faced by many students results at least in part from the design of US student loans. Specifically, loans are organised like a mortgage, with fixed monthly repayments over a fixed period of time, creating a high repayment burden on borrowers with low income. This paper draws on the experience of the income-contingent loan (ICL) systems operating in England and Australia, in which monthly repayments are related to the borrower's monthly income. By design, those systems explicitly include insurance against problems of repayment during periods of low income. We discuss the design of this type of loan in detail since such an exercise seems to be largely absent in the US literature. Drawing on data from the US Current Population Survey (CPS) we provide two main empirical contributions. First a stylised illustration of the revenue and distributional implications of different hypothetical ICL arrangements for the USA; and second an illustration of repayment problems faced by low-earning borrowers in the US loan system, including a plausible example of adverse outcomes in the Stafford loan. Importantly, we compare repayment burdens under the existing and alternative systems. Our illustrations show how US mortgage-style loans can create financial difficulties for a significant minority of US borrowers, difficulties which a well-designed ICL has significant potential to address.
Keywords: H28; I22; I28; J24; 330; income contingent loans; mortgage-type loans; student loan design; loan defaults; repayment burdens